2014
DOI: 10.1038/jcbfm.2014.173
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion in Insulin Resistance and Type 2 Diabetes

Abstract: Cerebral perfusion was evaluated in 87 subjects prospectively enrolled in three study groups-healthy controls (HC), patients with insulin resistance (IR) but not with diabetes, and type 2 diabetes mellitus (T2DM). Participants received a comprehensive 8-hour clinical evaluation and arterial spin labeling magnetic resonance imaging (MRI). In order of decreasing significance, an association was found between cerebral blood flow (CBF) and sex, waist circumference, diastolic blood pressure (BP), end tidal CO 2 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 37 publications
2
52
1
2
Order By: Relevance
“…The results did not reach an agreement yet. Some studies have reported decreased CBF in T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994), while others did not observe CBF alteration in T2DM (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011). Most of the studies reporting no CBF alteration in T2DM typically used large regions of interest (ROI) and/or did not adequately account for the potential risk factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results did not reach an agreement yet. Some studies have reported decreased CBF in T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994), while others did not observe CBF alteration in T2DM (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011). Most of the studies reporting no CBF alteration in T2DM typically used large regions of interest (ROI) and/or did not adequately account for the potential risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…ASL has been recently used to evaluate CBF in T2DM patients, however the reports are contradictory. Some studies found that resting CBF is similar between T2DM patients and controls (Tiehuis et al 2008; Rusinek et al 2015; Novak et al 2011), while others reported reduced CBF in patients with T2DM (Xia et al 2015; Novak et al 2006; Last et al 2007; Nagamachi et al 1994). The cross-sectional design of these studies however, did not allow to investigate the association between T2DM and changes in brain perfusion or structure and cognitive or mobility functions over time.…”
Section: Introductionmentioning
confidence: 99%
“…Although neuropsychological tests such as Mini-Mental State Examination and Montreal Cognitive Assessment remain to be the prevailing methods for evaluating T2DM patients with and without cognitive decline, a number of neuroimaging studies have emerged to investigate the compromised brain functions of T2DM patients by measuring changes in perfusion, 4 metabolism, 5 spontaneous brain activity at resting-state, 6 and functional connectivity. 7 The observed functional changes have been associated with sustained hyperglycemia and the resulting alterations in cerebral vasculature, neurotrophic factors, and neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%
“…Dado que los mayores ancianos institucionalizados y con diabetes, son más proclives al deterioro cognitivo en general (Awad, et al 2004;Arvanitakis et al, 2004;y Salinas-Contreras et al, 2013), y de la memoria en particular (Donohoe et al, 2000;Redondo et al, 2010;y Rusinek et al, 2015), podemos concluir que los ancianos con enfermedades metabólicas como la DM2 podrían beneficiarse de la participación en programas de estimulación de la memoria como proponen Best et al (1992) y Kliegl et al (1989), profundizando a la vez en la línea de la promoción del envejecimiento saludable en mayores institucionalizados (Cabaco y Crespo, 2015;Wobbeking, Cabaco, Urchaga, Sánchez, García, 2015).…”
Section: Discusión Y Conclusionesunclassified
“…Por otra parte, encontramos que la memoria episódica explícita se altera más que la memoria implícita en mayores diabéticos, en comparación con mayores no diabéticos (Redondo et al, 2010). Más recientemente, Rusinek et al (2015) obtienen rendimientos inferiores en tareas de memoria verbal y de memoria espacial, así como déficits en la velocidad del procesamiento verbal, en participantes con DM2 en comparación con sujetos sin DM2.…”
Section: Introductionunclassified